Original articleBrain metastases in paediatric patients – characteristics of a patient series and review of the literature - Stefanowicz, Joanna; Iżycka-Świeszewska, Ewa; Szurowska, Edyta; Bień, Ewa; Szarszewski, Adam; Liberek, Anna; Stempniewicz, Mirosław; Kloc, Wojciech; Adamkiewicz-Drożyńska, Elżbieta (Folia Neuropathologica, 2011)
In contrast to the occurrence of brain metastases advanced malignant tumours in adult cancer patients, the dissemination of solid tumours to the brains of paediatric cancer patients is very uncommon. We present a neuropathological and clinical study of a group of children and adolescents with brain metastases (BM) from extracranial solid malignancies. The analysed patients were diagnosed with soft tissue sarcomas (three), germ cell tumours (three), or osteosarcoma, neuroblastoma, clear cell sarcoma of the kidney, or pleuropulmonary blastoma (one each). In our series, BM frequently coexisted with pulmonary metastases. Three different metastatic patterns were discernible: a solitary tumour, multiple lesions and diffuse parenchymal dissemination. Two cases showed haemorrhagic presentation. Most of the children died due to BM progression, while children with germ cell tumours showed the best prognosis. The histopathological pictures of BM can be different from the primary tumour, showing dedifferentiation or a diverse neoplastic component. The autopsy examination can still be helpful in the final diagnosis of certain cases with atypical clinical presentations.